Flexible monoaryl methyl alpha-diimine palladium (II) catalyst and application thereof in ethylene catalytic polymerization

The flexible monoarylmethyl α-diimide palladium (II) catalyst improves the activity and branching density of polyethylene in ethylene polymerization, solves the problem of low activity of existing catalysts, and achieves high branching and wideness Molecular weight polymer production, suitable for viscosity adjustment and polar functional polymerization of lubricating oils.

CN119264190AActive Publication Date: 2025-01-07ANHUI NORMAL UNIV

Patent Information

Application Number
CN202411377146.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing hyperbranched polyethylene and polar functionalized polyethylene catalysts have low activity and low branching density during polymerization.

Method used

The catalyst is prepared by a specific synthetic route using a flexible monoarylmethyl α-diimine palladium (II) catalyst and is used in ethylene catalytic polymerization, combining tetrakis(3,5-bis(trifluoromethyl)benzene Sodium borate as a ligand regulates the polymerization reaction conditions to improve catalytic activity and branching density.

Benefits of technology

It significantly improves the catalytic activity and branching density of polyethylene, and produces polyethylene with high branching and wide molecular weight, which is suitable for regulating the viscosity of PAO lubricating oil base oil and exhibits excellent performance in copolymerization of ethylene with polar monomers. efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264190A_ABST
    Figure CN119264190A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible monoaryl methyl alpha-diimine palladium (II) catalyst and an application thereof in ethylene catalytic polymerization. According to the catalyst disclosed by the invention, 1, 2-acenaphthequinone and 2, 3-butanedione are taken as a core framework, and a flexible monoaryl methyl structure is ingeniously introduced, so that high branching degree and wide molecular weight adjustment of polyethylene are successfully realized. The polymerization activity is remarkable and is between 1.6 * 10 < 4 > g / (mol Pd.h) and 15.1 * 10 < 4 > g / (mol Pd.h). Especially, compared with traditional rigid o-aryl and o-diaryl methyl Pd (II) catalysts, the flexible catalyst provided by the invention can significantly improve the branching density, and provides a highly flexible means for adjusting the viscosity of PAO lubricant base oil. In the copolymerization reaction of ethylene and methacrylic acid, the flexible catalyst also shows excellent performance, the rigidity of the flexible catalyst is superior to that of the flexible catalyst in the aspect of promoting MA insertion, and the wide application prospect of the flexible catalyst in the synthesis of polar functionalized polyethylene is further verified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal catalysis and olefin polymerization, and specifically relates to a flexible monoarylmethyl α-diimine palladium (II) catalyst and application thereof in ethylene catalytic polymerization. Background Art

[0002] Hyperbranched polyethylene (HBPE) is a unique type of polyethylene characterized by a highly branched structure that improves solubility, reactivity and other physical properties, making it suitable for use in coatings, adhesives and viscosity modifiers. On the other hand, polar functionalized polyethylene (PFPE) is a chemically modified polyethylene that incorporates polar groups to improve compatibility, adhesion, wettability and other surface properties, and can be used in applications such as compatibilizers, coating additives and medical devices due to its biocompatibility.

[0003] Both HBPE and PFPE exhibit special properties that are different from traditional polyethylene. At present, late transition metal catalytic systems have made significant progress in the copolymerization of ethylene with polar monomers and the synthesis of HBPE. In addition, some important progress has been made in the synthesis of HBPE. Among them, α-diimine palladium catalysts have inherent advantages in the synthesis of HBPE, especially in the production of polar functionalized HBPE, and there is currently no other viable catalytic system to replace it. In this study, we introduced a new flexible monoarylmethyl α-diimine palladium catalyst specifically for the preparation of HBPE. Summary of the invention

[0004] In order to overcome the problems of low activity and low branching density of polymers obtained by polymerization of hyperbranched polyethylene and polar functionalized polyethylene catalysts in the prior art, the present invention provides a flexible monoarylmethyl α-diimine palladium (II) catalyst and its application in ethylene catalytic polymerization.

[0005] The flexible monoarylmethyl α-diimine palladium (II) catalyst of the present invention has a general structural formula as shown below:

[0006]

[0007] Wherein: R is selected from methyl or naphthyl; X1=Cl; X2=CH3, Et, n-Pr or n-Bu; R1, R2, R3 are independently selected from H, Me, Et, tBu, F, Cl, Br, OMe or CF3.

[0008] The flexible monoarylmethyl α-diimine palladium (II) catalyst of the present invention further preferably has the following structure:

[0009]

[0010] The synthetic route of the flexible monoarylmethyl α-diimine palladium (II) catalyst of the present invention is as follows:

[0011]

[0012] The specific steps include:

[0013] Step 1: Preparation of flexible monoaryl methylaniline compounds

[0014] The zinc powder was placed in a Schlenk tube, and anhydrous LiCl and dry oxygen-free THF were added in a controlled environment of a glove box. The Schlenk tube was removed from the glove box and the zinc was activated using 1,2-dibromomethane and TMSCl. Subsequently, the arylbenzobromide was introduced at ambient temperature and the reaction mixture was heated to 50 °C and kept overnight. Afterwards, the zinc crown acyl group was separated from the zinc powder by a syringe filter and retained as a THF solution for subsequent reactions. In a separate Schlenk tube, 2,6-dibromoaniline, 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl and Pd(OAc)2 were combined and degassed. THF was added, the mixture was stirred until a color change to red was observed, the first step solution in THF was added dropwise, and the reaction mixture was stirred at room temperature for 2 hours before being quenched with saturated aqueous NH4Cl. The product was then extracted using ether (3×50 mL). The combined organic extracts were washed with thiourea aqueous solution and dried over MgSO4, and finally the solvent was removed and purified by flash column chromatography (PE:EA=10:1) to obtain flexible monoarylmethylaniline compounds as white solids.

[0015] Step 2: Preparation of catalyst ligands

[0016] 2a. A solution of a flexible monoaryl methylaniline compound, 1,2-acenaphthenequinone and acetic acid was dissolved in acetonitrile, and the mixture was stirred continuously at 80°C for 48 hours. During the reaction, samples were collected regularly every 6 hours and monitored on the TLC plate. This process continued until a clear spot appeared on the TLC plate, indicating that the reaction was complete. Subsequently, the solvent was evaporated and concentrated to 10 mL under vacuum conditions, and the concentrated solution was diluted in methanol (100 mL) to form a yellow solid precipitate. After filtering and separating the solid, the catalyst ligand L1 or L3 was obtained by vacuum drying as a yellow solid powder.

[0017] Among them, the molar ratio of the flexible monoaromatic methylaniline compound to 1,2-acenaphthenequinone is 2:0.9.

[0018] 2b, the solution of flexible monoaryl methylaniline compounds, 2,3-dimethylglyoxal and acetic acid was dissolved in ethanol, and stirred 48 hours under the same conditions. In the reaction process, samples were regularly collected every 6 hours, and monitored on the TLC plate. This process continued until an obvious spot appeared on the TLC plate, indicating that the reaction was completed. Subsequently, the evaporating solvent was concentrated to 10mL under vacuum, and the gained concentrated solution was diluted in methanol (100mL) to form a yellow solid precipitate. After filtering and separating solid, catalyst ligand L2 or L4 was obtained by vacuum drying, which was a yellow solid powder.

[0019] The molar ratio of the flexible monoaromatic methylaniline compound to 2,3-butanedione is 2:0.9.

[0020] Step 3: Preparation of Catalyst

[0021] Under nitrogen protection, the catalyst ligand obtained in step 2 was mixed with (COD)PdMeCl in dichloromethane as solvent. After stirring at room temperature for 12 hours, the suspension was filtered, the mother liquor was freed of solvent under vacuum, washed with ether, and dried under vacuum to obtain a yellow powdery solid complex.

[0022] The preparation method of (COD)PdMeCl is as follows: palladium chloride is dissolved in concentrated hydrochloric acid, ethanol is added, 1,4-cyclooctadiene (COD) is injected, the system turns yellow, and a yellow solid is obtained by filtration. The yellow solid is reacted with dichloromethane and tetramethyltin at room temperature until the yellow color disappears. After filtration, the filtrate is pumped to a small volume, dichloromethane is added to precipitate a white solid, which is washed with ether and the solvent is removed to obtain a white solid powder (COD)PdMeCl.

[0023] In step 1, the molar ratio of Zn powder, LiCl, 1,2-dibromomethane, TMSCl and aryl benzobromide is 1.4:1:0.05:0.01:1, and the molar ratio of 2,6-dibromoaniline, Sphos, Pd(OAc)2 and zinc oxide solution is 1:0.02:0.01:2.4. The developing solvent used for column chromatography purification is petroleum ether:ethyl acetate=10:1.

[0024] The flexible monoarylmethyl α-diimine palladium (II) catalyst of the present invention uses 1,2-acenaphthenequinone or 2,3-butanedione as the catalyst skeleton, and introduces a flexible monoarylmethyl group into the skeleton, so as to have better activity.

[0025] The invention discloses an application of the flexible monoarylmethyl alpha-diimine palladium (II) catalyst in catalyzing ethylene polymerization to prepare high-branched polyethylene.

[0026] Furthermore, the catalytic reaction system also includes sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (NaBArF).

[0027] The molar ratio of the flexible monoarylmethyl α-diimine palladium (II) catalyst to NaBArF is 1:2.

[0028] Polymerization conditions: catalyst 10.0 μmol, NaBArF=2.0 eq, ethylene pressure 4 atm.

[0029] The reaction temperature is 0-150°C, and the reaction time is 1-12 hours.

[0030] The invention discloses an application of high-branched polyethylene prepared by catalyzing ethylene polymerization using the flexible monoarylmethyl α-diimine palladium (II) catalyst in regulating the viscosity of polyα-olefin base oil.

[0031] The invention discloses an application of the flexible monoarylmethyl α-diimine palladium (II) catalyst in catalyzing the copolymerization of ethylene and polar monomers.

[0032] Furthermore, the catalytic reaction system also includes sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (NaBArF).

[0033] The molar ratio of the flexible monoarylmethyl α-diimine palladium (II) catalyst to NaBArF is 1:2.

[0034] The polar monomer includes methyl acrylate.

[0035] Polymerization conditions: catalyst 20.0 μmol, NaBArF=2.0 eq, methyl acrylate 1 M-2 M, ethylene pressure 2 atmospheres.

[0036] The polymerization temperature is 0-150°C and the reaction time is 1-12 hours.

[0037]

[0038] In ethylene polymerization, these catalysts produced polyethylene with a high degree of branching (79-95 / 1000) and molecular weights ranging from 7.7 to 144.4 kg / mol. The polymerization activities ranged from 1.6 to 15.1 × 10 4 g / (mol Pd·h). When used with rigid o-aryl and o-diaryl methyl Pd(II) catalysts ( Figure 1 ) were placed in juxtaposition, the flexible catalyst of the present invention significantly increased the branching density (94: 28-34 / 1000). These highly branched polyethylenes can effectively adjust the viscosity of PAO lubricant base oils. Similar trends were observed in the copolymerization of ethylene and MA. In addition, the flexible Pd(II) catalyst of the present invention showed excellent efficiency in promoting MA insertion during the copolymerization of ethylene and MA, which was superior to its rigid analogues.

[0039] Experiments have shown that in the ethylene polymerization reaction, the reaction temperature is controlled at 10-70°C and the reaction time is 1-12h. During homopolymerization, the Pd2 and Pd4 complexes based on diacetyl show high catalytic activity, reaching 10 5 g / (mol Pd·h) and produced polyethylene with high molecular weight (Mn up to 144 kg / mol) and highly branched structure (BD = 84-95 / 1000C). In contrast, the Pd1 and Pd3 catalysts based on acenaphthenequinone showed 10 4 g / (mol Pd h), producing polyethylene of medium molecular weight (Mn up to 15 kg / mol) and similar branching structure (79-120 / 1000C) under given polymerization conditions. It is noteworthy that with increasing temperature, both the catalytic activity and the branching density of polyethylene increase, while its molecular weight decreases. However, it is worth mentioning that the branching density increases only slightly, mainly due to the higher chain walking rate and chain growth rate inherent to the α-diimine palladium catalyst system. For catalysts Pd1-Pd4, the backbone structure plays a key role in ethylene polymerization. Under the specified experimental conditions, the activities of butyl-supported catalysts Pd2 and Pd4 are significantly enhanced by 4-10 times compared with their acenaphthene-based counterparts Pd1 and Pd3. This enhanced activity translates into the production of polyethylene with 4-10 times higher molecular weight. However, it is noteworthy that the backbone structure has little effect on the branching density of the produced polyethylene, indicating that it is challenging to regulate this aspect. In addition, the introduction of different monoarylmethyl substituents also affects the polymerization process. Under similar polymerization conditions, phenyl palladium catalysts, such as Pd1 and Pd2, consistently produce polyethylene with higher branching density than naphthyl palladium catalysts Pd3 and Pd4. In addition, the molecular weight of the polyethylene is affected by the backbone; the axial phenyl substituents lead to lower molecular weight for the acenaphthenequinone backbone, while the butyl backbone has a higher molecular weight. This observation may be explained by a combination of chain transfer and chain growth mechanisms that are unique to the different backbone structures. It is worth mentioning that catalysts Pd-Ph and Pd-CHPh2 effectively produce polyethylene with significantly lower branching density, with 28 to 34 branches per 1000 carbon atoms ( Figure 2 ). Its branching density is much lower than that observed for the currently used flexible monoarylmethyl catalysts Pd1-Pd4. This interesting observation suggests that the flexible monoarylmethyl α-diimine Pd(II) system plays a key role in influencing the microstructure of the resulting polymer. This effect may arise from the ability of the flexible substituents to create a more accessible environment for the catalytic center, which may promote the formation of branches. 13 C NMR spectroscopy analysis showed that the polyethylene produced by the flexible monoarylmethyl catalyst system was hyperbranched and contained various branching types, mainly long-chain branches.

[0040] The copolymerization of olefins and polar monomers in the presence of α-diimine palladium catalysts facilitates the direct synthesis of polar functionalized polyolefins. In this study, we used catalysts Pd1–Pd5 for the copolymerization of ethylene with methyl acrylate (MA). Our observations revealed relatively low catalytic activity (levels of 10 3 g mol -1 h -1 ), producing E-MA copolymers with low to medium molecular weight (ranging from 4.1 to 24.4 kg / mol) and medium MA incorporation ratios (1.54-5.52 mol%). As the initial MA concentration increased, the catalytic activity and copolymer molecular weight decreased, while the MA incorporation ratio increased significantly. For catalysts Pd1-Pd4, the backbone structure also plays a crucial role in the copolymerization of ethylene with MA. Under the specified experimental conditions, butyl-supported catalysts Pd2 and Pd4 showed poor copolymerization ability with MA compared with their acenaphthenequinone-based analogs Pd1 and Pd3. The effect of the backbone on activity and molecular weight is complex and varies at different MA concentrations, which is in significant contrast to its effect on ethylene homopolymerization. It is worth noting that the branching density of the obtained copolymers is consistent with the branching intensity observed in ethylene homopolymerization and is largely unaffected by the backbone type. In addition, the introduction of different monoaromatic methyl substituents affects the copolymerization process. Phenyl palladium catalysts, including Pd1 and Pd2, showed excellent activity under similar polymerization conditions and produced E-MA copolymers with higher branching density than the naphthyl palladium catalysts Pd3 and Pd4. In addition, the copolymers obtained using phenyl catalysts generally had higher molecular weights than those produced using naphthalene catalysts, which is in sharp contrast to the trend observed in ethylene homopolymerization. However, the insertion rate of MA was relatively insensitive to the axial substituent.

[0041] Compared to ethyl palladium catalysts, recently introduced monoaryl methyl catalysts proved to be superior in homopolymerization, exhibiting higher catalytic activity and producing polyethylene with fewer branches but higher molecular weight. This improvement suggests that the incorporation of the aryl group increases the efficiency of the catalyst in chain growth while suppressing chain transfer. In copolymerization, phenyl Pd1 showed higher activity than ethyl palladium catalysts, producing E-MA copolymers with higher molecular weight, lower branching density, and lower MA insertion.

[0042] The catalyst of the present invention is uniquely designed, with 1,2-acenaphthenequinone and 2,3-butanedione as the core skeleton, and by ingeniously introducing a flexible monoaryl methyl structure, it successfully achieves high branching degree (range 79-95 / 1000) and wide molecular weight regulation (7.7 to 144.4 kg / mol) of polyethylene. Its polymerization activity is significant, ranging from 1.6 to 15.1×10 4g / (mol Pd·h). In particular, compared with traditional rigid o-aryl and o-diaryl methyl Pd(II) catalysts, the flexible catalyst of the present invention can significantly increase the branching density (up to 94 / 1000C, compared with 28-34 / 1000C), providing a highly flexible means for adjusting the viscosity of PAO lubricant base oil. In the copolymerization of ethylene and methacrylic acid (MA), the flexible catalyst also exhibits excellent performance, not only outperforming its rigid counterparts in promoting MA insertion, but also further verifying its broad application prospects in the synthesis of polar functionalized polyethylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Advantages of flexible monoarylmethyl catalysts in the synthesis of HBPE and polar functionalized HBPE.

[0044] Figure 2 Comparison of branching density of polyethylene produced by Pd2, Pd-Ph and Pd-CHPh2 at 30 °C.

[0045] Figure 3 Comparison of branching density and MA incorporation rate of polyethylene prepared with Pd2, Pd-Ph and Pd-CHPh2 at 30°C.

[0046] Figure 4 The polyethylene prepared by the catalyst of Example 1 at 30°C 1 H NMR (Table 1, entry 1).

[0047] Figure 5 The polyethylene prepared by the catalyst of Example 2 at 30°C 13 C NMR (Table 1, entry 3).

[0048] Figure 6 The polyethylene prepared by the catalyst of Example 1 under 2M MA 13 C NMR (Table 2, entry 2). DETAILED DESCRIPTION

[0049] In order to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0050] The synthesis steps involved in the examples are preferred catalyst synthesis steps, and the synthesis steps of non-preferred catalysts are not disclosed.

[0051] Reagents and raw materials used in the examples: All metal organic reactions were carried out under nitrogen protection, and all solvents were dried and deoxygenated. Anhydrous methanol and ethanol were analytically pure and used directly. Toluene was dehydrated by molecular sieve, refluxed with sodium metal under nitrogen protection, and evaporated before use.

[0052] Embodiment 1:

[0053] 1. Synthesis of 2,6-dibenzylaniline (A1)

[0054] Zinc powder (919 mg, 14.0 mmol, 1.4 equiv) was placed in a Schlenk tube, and then anhydrous LiCl (426 mg, 10 mmol, 1.0 equiv) and dry oxygen-free THF (10 mL) were added in a controlled environment of a glove box. The Schlenk tube was then taken out of the glove box, and zinc was activated using 1,2-dibromomethane (93 mg, 0.5 mmol, 5 mol%) and TMSCl (10.9 mg, 0.1 mmol, 1 mol%). Subsequently, 2-benzyl bromide (10 mmol, 1.0 equiv) was introduced at ambient temperature. The reaction mixture was then heated to 50 ° C and kept overnight. Afterwards, the zinc crown acyl group was separated from the zinc powder by a syringe filter and retained as a THF solution for subsequent reactions. In a separate Schlenk tube, 2,6-dibromoaniline (3.8mmol, 1.0 equivalent), 2-dicyclohexylphosphine-2', 6'-dimethoxybiphenyl (SPhos, 76μmol, 2mol%) and Pd(OAc)2 (38umol, 1mol%) were combined and degassed. THF (5 ml) was added and the mixture was stirred until a color change to red was observed. The first step solution (9.2 mmol, 2.4 equivalent) in THF was gradually added dropwise. The reaction mixture was stirred at room temperature for 2 hours before being quenched with saturated NH4Cl aqueous solution. The product was then extracted using ether (3x 50mL). The combined organic extracts were washed with thiourea aqueous solution and dried with MgSO4. Finally, the aromatic amide was isolated as a white solid with a yield of 56% after removal of the solvent and purification (PE:Et=10:1) by flash column chromatography.

[0055] The reaction route is as follows:

[0056]

[0057] NMR analysis: 1H NMR (400MHz, CDCl3) δ7.36-7.30(d,J=7.9Hz,1H,Ar-H),7.28(d,J=1.5Hz,2H,Ar-H),7.20(m,J=15.5,7.3,5.7 Hz,7H,Ar-H),7.00(d,J=7.5Hz,2H,Ar-H),6.76(t,J=7.5Hz,1H,Ar-H),3.90(s,4H,-CH2-),3.45(s,2H,-NH2). 13 C NMR (101MHz, CDCl3) δ142.94,139.32,139.32,129.43,129.43,128.77,128.61,128.60,128.60,128. 47,128.46,128.46,128.46,126.31,126.31,125.09,118.14,118.14,38.16(-CH2-),38.16(-CH2-).

[0058] 2. Synthesis of catalyst ligand (L1)

[0059] A solution of A1 (2 mmol, 2.0 equiv.), 1,2-acenaphthenequinone (0.9 mmol, 0.9 equiv.) and acetic acid (5 ml) was dissolved in acetonitrile (10 ml). The mixture was stirred continuously at 80 °C for 48 h. During the stirring process, samples were collected regularly every 6 hours and monitored on the TLC plate. This process continued until a clear spot appeared on the TLC plate, indicating that the reaction was complete. Subsequently, the solvents from both reactions were evaporated and concentrated to 10 mL under vacuum. The resulting concentrated solution was then diluted in methanol (100 mL) to form a yellow solid precipitate. After filtration, it was washed with 10 mL of ethanol and dried in vacuo to obtain a yellow solid powder (L1) with a yield of 67%. The reaction route is shown below:

[0060]

[0061] NMR analysis: 1 H NMR (400MHz, CDCl3) δ7.73 (d, J=8.3Hz, 2H, Ar-H), 7.23-7.01 (m, 16H, Ar-H), 6.89 (t, J=7.5Hz, 8H, Ar-H), 6.80 (t ,J=7.3Hz,4H,Ar-H),6.45(d,J=7.1Hz,2H,Ar-H),4.03(d,J=15.3Hz,4H,-CH2-),3.78(d,J=15.5Hz,4H,-CH2-). 13C NMR (101MHz, CDCl3) δ162.46 (-C=N),148.74,143.58,140.21,139.96,139.42,137.90,136.74,135.97,135.36,13 3.26,130.47,130.13,130.06,129.93,129.88,129.53,129.44,129.27,129.09,129.04,128.96,128.82,128.71, 128.59,128.58,128.35,128.13,127.95,127.73,127.69,127.40,127.19,126.41,126.30,125.55,125.08,124.2 6,124.24,124.12,124.09,123.87,123.12,122.87,122.77,122.75,122.62,37.79(-CH2-).APCI-MS(m / z):calcd forC 52 H 40 N2:693.3270,Found,693.3254,[M+H] + .

[0062] 3. Synthesis of Pd1 complex

[0063] The Pd1 complex was synthesized by reacting (COD)PdMeCl (where COD represents 1,4-cyclooctadiene) with the corresponding ligand in dichloromethane. In a nitrogen atmosphere, 0.2mmol of ligand L1 was dissolved in 10mL of dichloromethane, and then (COD)PdMeCl (0.18mmol, 47.7mg) was added to the above solution. The resulting mixture was stirred at room temperature overnight. Most of the solvent was evaporated under reduced pressure, washed with 4×5mL of ether, filtered, and vacuum dried to obtain an orange-red solid product Pd1 with a yield of 72%. The reaction route is shown below:

[0064]

[0065] NMR analysis: 1H NMR(400MHz,CDCl3)δ7.83(t,J=8.5Hz,2H,Ar-H),7.34(t,J=7.7Hz,1H,Ar-H),7.28(d,J=1.9Hz,1H,Ar-H),7.24(d,J=2.2Hz,1H,Ar-H),7.22-7.12(m,9H,Ar-H),7.06(d,J=7.5Hz,4H,Ar-H),6.84(dt,J=11.6,7.5Hz,8H,Ar-H),6.73(q,J=7.2Hz,4H,Ar-H),6.47(d,J=7.2Hz,1H,Ar-H),6.18(d,J=7.3Hz,1H,Ar-H),4.37(d,J=15.6Hz,2H,

[0066] -CH2-),4.31-4.11(m,4H,-CH2-),4.02(d,J=15.6Hz,2H,-CH2-),0.94(s,3H,Pd-CH3). 13 C NMR(101MHz,CDCl3)δ173.19(-C=N),168.59(-C=N),143.64,143.42,142.71,142.68,139.52,139.36,138.43,132.67,132.52,132.02,131.58,131.52,131.47,131.15,130.83,130.60,130.46,130.45,130.23,130.19,129.98,129.72,129.48,129.37,128.92,128.73,128.46,128.17,128.05,127.95,127.81,127.79,127.58,127.45,127.14,126.90,126.83,126.72,126.21,125.98,125.75,125.68,124.92,124.46,124.13,124.04,38.21(-CH2-),3.24(Pd-CH3).MALDI-TOF-MS(m / z):calcd for C 52 H 40 N2Pd:798.2221,Found,798.2237,[M-Cl-Me] + .Elemental analysis:calc.for C 53 H 43ClN2Pd:C,74.91;H,5.10;N,3.30.Found:C,74.83;H,5.03;N,3.23.

[0067] Embodiment 2:

[0068] 1. Synthesis of 2,6-dibenzylaniline (A1)

[0069] The operation is the same as step 1 of Example 1.

[0070] NMR analysis: 1 H NMR (400MHz, CDCl3) δ7.36-7.30(d,J=7.9Hz,1H,Ar-H),7.28(d,J=1.5Hz,2H,Ar-H),7.20(m,J=15.5,7.3,5.7 Hz,7H,Ar-H),7.00(d,J=7.5Hz,2H,Ar-H),6.76(t,J=7.5Hz,1H,Ar-H),3.90(s,4H,-CH2-),3.45(s,2H,-NH2). 13 C NMR (101MHz, CDCl3) δ142.94,139.32,139.32,129.43,129.43,128.77,128.61,128.60,128.60,128. 47,128.46,128.46,128.46,126.31,126.31,125.09,118.14,118.14,38.16(-CH2-),38.16(-CH2-).

[0071] 2. Synthesis of catalyst ligand (L2)

[0072] A solution of A1 (2 mmol), 2,3-butanedione (0.9 mmol) and acetic acid (1 ml) was dissolved in ethanol (5 mL) and stirred for 48 hours under the same conditions. The remaining operations were the same as step (3) of Example 1, with a yield of 65%. The reaction scheme is as follows:

[0073]

[0074] NMR analysis: 1 H NMR (400MHz, CDCl3) δ7.40(d,J=1.2Hz,1H,Ar-H),7.37-7.30(m,8H,Ar-H),7.25(d,J=7.6Hz,11H,Ar-H),7.17(m,J=6.0Hz,6H,Ar-H),3.87(d,J=15.4Hz,4H,

[0075] -CH2-),3.75(d,J=15.4Hz,4H,-CH2-),1.64(s,6H,-CH3). 13 C NMR(101MHz, CDCl3)δ168.60(-C=N),147.89,140.19,128.91,128.45,128.36,128.00,125.97,123.30,37.89(-CH2-),16.15(-CH3).APCI-MS(m / z):calcd for C 44 H 40 N2:597.3270,Found,597.3248,[M+H] + .

[0076] 3. Synthesis of Pd2 complex

[0077] L1 in step 3 of Example 1 was replaced by L2, and the remaining operations were the same as step 3 of Example 1, with a yield of 85%. The reaction route is as follows:

[0078]

[0079] NMR analysis: 1 H NMR (400MHz, CDCl3) δ7.27(s,2H,Ar-H),7.25(s,4H,Ar-H),7.18(m,J=6.6Hz,18H,Ar-H),7.11(d,J=7.4Hz,2H,Ar-H),4.24(d,J= 15.7Hz,2H,-CH2-),4.18-4.03(m,4H,-CH2-),3.96(d,J=15.5Hz,2H,-CH2-),0.80(s,3H,-CH3),0.64(d,J=12.6Hz,6H,Pd-CH3). 13 C NMR (101MHz, CDCl3) δ176.54(-C=N),171.47(-C=N),143.73,143.34,139.97,138.95,131.52,130.80,129.46,129.37,129.05,12 8.73,128.66,128.48,127.08,126.56,126.50,126.23,38.30(-CH2-),38.06(-CH2-),19.38(-CH3),18.54(-CH3),2.72(Pd-CH3).

[0080] MALDI-TOF-MS(m / z):calcd for C 44 H 40N2Pd:702.2221,Found,702.2235,[M-Cl-Me] + .

[0081] Elemental analysis:calc.for C 45 H 43 ClN2Pd:C,71.71;H,5.75;N,3.72.Found:C,71.65;H,5.67;N,3.82.

[0082] Embodiment 3:

[0083] 1. Synthesis of 2,6-bis(naphthalene-2-ylmethyl)aniline (A2)

[0084] The 2-benzyl bromide in step 1 of example 1 was replaced by 2-(bromomethyl)naphthalene, and the remaining operations were the same as step 1 of example 1, with a yield of 42%.

[0085] NMR analysis: 1 H NMR (400MHz, CDCl3) δ8.02-7.51(m,8H,Ar-H),7.49-7.22(m,6H,Ar-H),7.11(d,J=7 .5Hz,2H,Ar-H),6.84(t,J=7.5Hz,1H,Ar-H),4.09(s,4H,-CH2-),3.52(s,2H,-NH2). 13 C NMR (101MHz, CDCl3) δ143.19,137.01,136.87,133.57,133.04,132.25,130.12,129.64,128.88,128.30,127.76,127.60,127.50,127.39 ,127.32,127.24,127.16,127.10,126.77,126.66,126.58,126.10,126.02,125.43,125.09,118.28,38.44(-CH2-).ACPI-MS(m / z):calcd for C 28 H 24 N:374.1909,Found,374.1864,[M+H] + .

[0086] 2. Synthesis of catalyst ligand (L3)

[0087] A1 in step 2 of Example 1 was replaced by A2, and the remaining operations were the same as step 2 of Example 1, with a yield of 62%.

[0088] NMR analysis:1 H NMR (400MHz, CDCl3) δ7.44(d,J=8.0Hz,8H,Ar-H),7.36(d,J=8.4Hz,4H,Ar-H),7.29(d,J=8.2Hz,4H,Ar-H),7.25-7.09(m, 20H, Ar-H), 6.86 (t, J = 7.7Hz, 2H, Ar-H), 6.36 (d, J = 7.1Hz, 2H, Ar-H), 4.24 (d, J = 15.3Hz, 4H, -CH2-), 4.02 (d, J = 15.3Hz, 4H,

[0089] -CH2-). 13 C NMR (101MHz, CDCl3) δ162.68 (-C=N),148.88,139.58,137.64,133.12,131.61,128.62,128.44,128.31,128.14,127 .84,127.79,127.51,127.20,127.00,126.65,125.49,124.84,123.89,122.31,38.07(-CH2-).APCI-MS(m / z):calcd forC 68 H 48 N2:893.3896,Found,893.3865,

[0090] [M+H] + .

[0091] 3. Synthesis of Pd3 complex

[0092] L1 in step 3 of Example 1 was replaced by L3, and the remaining operations were the same as step 3 of Example 1, with a yield of 69%.

[0093] NMR analysis: 1H NMR (400MHz, CDCl3) δ7.59(s,2H,Ar-H),7.50-7.39(m,6H,Ar-H),7.38-7.31(m,7H,Ar-H), 7.31-7.26(m,7H,Ar-H),7.24-7.00(m,14H,Ar-H),6.89(t,J=7.7Hz,1H,Ar-H),6.70(t,J=7 .7Hz,1H,Ar-H),6.43(d,J=7.1Hz,1H,Ar-H),5.98(d,J=7.2Hz,1H,Ar-H),4.66(d,J=15.7Hz ,2H,-CH2-),4.57-4.30(m,4H,-CH2-),4.25(d,J=15.4Hz,2H,-CH2-),1.01(s,3H,Pd-CH3). 13 C NMR(101MHz, CDCl3)δ173.40(-C=N),168.71(-C=N),143.83,142.87,142.50,137.22,136.19,133.08,1 32.90,132.42,131.63,131.53,131.29,129.62,129.58,129.15,129.06,128.16,128.02,127.95,127.7 5,127.66,127.60,127.53,127.19,127.13,127.07,127.03,126.91,126.77,125.77,125.58,125.12,12 4.95,124.88,123.41,123.31,38.58(-CH2-),38.09(-CH2-),3.61(Pd-CH3).MALDI-TOF-MS(m / z):calcd for C 68 H 48 N2Pd:998.2847,Found,998.2863,[M-Cl-Me] + .Elemental analysis:calc.for C 69 H 51 ClN2Pd:C,78.93;H,4.90;N,2.67.Found:C,78.76;H,4.69;N,2.61.

[0094] Embodiment 4:

[0095] 1. Synthesis of 2,6-bis(naphthalene-2-ylmethyl)aniline (A2)

[0096] The operation was the same as step 1 in Example 3, with a yield of 42%.

[0097] NMR analysis: 1 H NMR (400MHz, CDCl3) δ8.02-7.51(m,8H,Ar-H),7.49-7.22(m,6H,Ar-H),7.11(d,J=7 .5Hz,2H,Ar-H),6.84(t,J=7.5Hz,1H,Ar-H),4.09(s,4H,-CH2-),3.52(s,2H,-NH2). 13 C NMR (101MHz, CDCl3) δ143.19,137.01,136.87,133.57,133.04,132.25,130.12,129.64,128.88,128.30,127.76,127.60,127.50,127.39 ,127.32,127.24,127.16,127.10,126.77,126.66,126.58,126.10,126.02,125.43,125.09,118.28,38.44(-CH2-).ACPI-MS(m / z):calcd for C 28 H 24 N:374.1909,Found,374.1864,[M+H] + .

[0098] 2. Synthesis of catalyst ligand (L4)

[0099] A1 in step 2 of Example 2 was replaced by A2, and the remaining operations were the same as step 2 of Example 1, with a yield of 60%.

[0100] NMR analysis: 1 HNMR (400MHz, CDCl3) δ7.75 (dt, J=16.6, 8.7Hz, 2H, Ar-H), 7.68-7.54 (m, 11H, A r-H),7.50(s,3H,Ar-H),7.46-7.39(m,1H,Ar-H),7.37-7.29(m,7H,Ar-H),7.20 (dd,J=8.4,1.6Hz,4H,Ar-H),7.13-7.03(m,4H,Ar-H),6.99(dd,J=8.5,6.5Hz,2 H, Ar-H), 4.07 (s, 1H, -CH2-), 3.76 (q, J = 15.5Hz, 7H, -CH2-), 1.53 (s, 6H, -CH3). 13 C NMR (101MHz,CDCl3)δ

[0101] 168.56(-C=N),147.89,137.70,133.49,131.98,129.65,128.93,128.61,128.31,127.99,127.60,1 27.51,127.42,127.19,125.91,125.23,123.42,37.99(-CH2-),16.37(-CH3).APCI-MS(m / z):calcd for C 60 H 48 N2:797.3896,Found,797.3862,[M+H] + .

[0102] 3. Synthesis of Pd4 complex

[0103] L1 in step 3 of Example 1 was replaced by L4, and the remaining operations were the same as step 3 of Example 1, with a yield of 83%.

[0104] NMR analysis: 1 H NMR (400MHz, CDCl3) δ7.75-7.57(m,16H,Ar-H),7.48(m,2H,Ar-H),7.44-7.30 (m,10H,Ar-H),7.27-7.17(m,6H,Ar-H),4.48(d,J=15.7Hz,2H,-CH2-),4.39-

[0105] 4.26(m,4H,-CH2-),4.15(d,J=15.6Hz,2H,-CH2-),0.78(s,3H,-CH3),0.56(s,3H,-CH3),0.35(s,3H,Pd-CH3). 13 C NMR(101MHz, CDCl3)δ176.30(-C=N),171.27(-C=N),143.77,143.69,143.40,137.48,136.43 ,133.42,133.38,132.03,131.53,130.79,129.21,128.95,128.44,128.25,128.03,127.67, 127.49,127.41,127.36,127.28,127.17,126.64,126.41,126.15,125.84,125.56,38.59(-C H2-),38.24(-CH2-),19.44(-CH3),18.60(-CH3),2.96(Pd-CH3).MALDI-TOF-MS(m / z):calcd for C 60 H 48N2Pd:902.2847,Found,902.2886,[M-Cl-Me] + .Elemental analysis:calc.for C 61 H 51 ClN2Pd:C,76.80;H,5.39;N,2.94.Found:C,76.67;H,5.26;N,2.78.

[0106] Example 5: Application of Pd1-Pd4 in catalytic ethylene polymerization

[0107] General procedure for ethylene homopolymerization: First, a 350 mL thick-walled pressure glass reactor connected to a high-pressure gas line was vacuum dried at 90 °C for at least 1 hour. The reactor was then adjusted to the desired polymerization temperature. 38 mL of CH2Cl2 and the required amount of NaBArF were added to the reactor under N2 atmosphere, and then the required amount of catalyst in 2 mL of CH2Cl2 was injected into the polymerization system through a syringe. Under rapid stirring, the reactor was pressurized and maintained under 4 atm of ethylene. After the desired time, the pressure reactor was vented and the polymer was dried overnight under vacuum.

[0108] General procedure for copolymerization of methyl acrylate with ethylene: In a typical experiment, a 350 mL thick-walled pressure glass reactor connected to a high-pressure gas line was first dried under vacuum at 90 °C for at least 1 hour. The reactor was then adjusted to the desired polymerization temperature. 18 mL of dichloromethane and the required amount of NaBArF were added to the reactor under N2 atmosphere, and then the required amount of MA and Pd catalyst in 2 mL of CH2Cl2 were injected into the polymerization system by syringe. Under rapid stirring, the reactor was pressurized and maintained under ethylene pressure of 2 atm. After 12 hours, the pressure reactor was vented and the copolymer was dried under vacuum overnight.

[0109] The following table shows the experimental conditions for ethylene polymerization using the preferred catalyst provided by the present invention; catalyst (Cat.), temperature (T), yield (Yield), catalytic activity (Act.), polymer molecular weight (M n ), polymer molecular weight distribution (PDI), degree of branching (brs) and other polymerization result data.

[0110] Table 1 Effect of catalyst and temperature on ethylene polymerization.

[0111]

[0112] a Polymerization conditions: catalyst 10.0 μmol, NaBArF = 2.0 eq, dichloromethane = 40 mL, ethylene pressure 4 atm, time = 3 hours;

[0113] b The unit of activity is 10 4 g mol -1 h -1 ;

[0114] c Polymer molecular weight M n and molecular weight distribution PDI were determined by gel permeation chromatography (GPC) at 40 °C in tetrahydrofuran and polystyrene standards;

[0115] d The degree of branching refers to the number of branches per 1000 carbon atoms, which is 1 H NMR nuclear magnetic resonance determination;

[0116] Table 2 Copolymerization of ethylene MA and palladium catalyst

[0117]

[0118] a Polymerization conditions: catalyst 20.0 μmol, NaBArF = 2.0 eq, DCM + MA = 20 mL, ethylene pressure 2 atm, time = 12 h, temperature = 30 °C;

[0119] b The unit of activity is 10 3 g mol -1 h -1 ;

[0120] cPolymer molecular weight M n and molecular weight distribution PDI were determined by gel permeation chromatography (GPC) at 40 °C in tetrahydrofuran and polystyrene standards;

[0121] The degree of branching refers to the number of branches per 1000 carbon atoms, which is 1 Determined by HNMR nuclear magnetic resonance method.

[0122] As shown in Table 1, a new class of flexible monoarylmethyl α-diimine Pd(II) catalysts has been successfully designed and synthesized for the production of hyperbranched polyethylene and polar functionalized polyethylene. In the ethylene polymerization reaction, butyl-based Pd2 and Pd4 catalysts showed high catalytic activity (10 5 g·mol -1 ·h -1 ) and produced high molecular weight, highly branched polyethylene (Mn up to 144 kg / mol). In contrast, the acenaphthenequinone-derived Pd1 and Pd3 catalysts showed 10 4 g·mol-1·h -1The moderate catalytic activity of the catalyst was 1.5 times that of the rigid Pd(II) catalyst reported previously ( Figure 3 ) compared to the flexible monoarylmethyl catalysts. The structural backbone of the catalyst and its axial monoarylmethyl component as well as the polymerization conditions play a key role in ethylene polymerization. Similar observations were made in the copolymerization of ethylene with MA in Table 2. It is noteworthy that these flexible monoarylmethyl catalysts are superior to the rigid catalysts ( Figure 3 ) can be inserted into MA more effectively. 13 C NMR spectroscopy confirmed the hyperbranched nature of the obtained (co)polymers.

[0123] Example 6: Study on the viscosity adjustment effect of HBPE in PAO base oil

[0124] In this study, the polymer HBPE is a high-viscosity polyolefin liquid that shows great potential in increasing the viscosity of polyalphaolefin (PAO) base oils. To explore this application, we systematically blended different masses of HBPE (Table 1, entry 4) into INEOS's PAO20 base oil, aiming to adjust its kinematic viscosity, as shown in Table 3. With the increase in the HBPE mass ratio, the kinematic viscosity of the resulting blends increased significantly at 40°C and 100°C, showing a positive correlation with the HBPE content. It is worth noting that although the viscosity index decreased slightly, it was still at a high level, meeting the strict requirements of synthetic lubricants. This experiment highlights the strong applicability of the HBPE synthesized in this study in fine-tuning the viscosity distribution of PAO lubricant base oils, thereby having great potential for industrial applications.

[0125] Table 3 Study on the viscosity regulation effect of HBPE in PAO base oil

[0126]

[0127] The above is a detailed introduction to a preferred compound, complex catalyst, catalyst composition and method for preparing an olefin polymer provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention, but the present invention is not limited to the specific implementation methods described herein. It is understood by those skilled in the art that other changes and modifications may be made without departing from the scope of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A flexible monoarylmethyl α-diimine palladium (II) catalyst, characterized in that Its general structure is shown below: Wherein: R is selected from methyl or naphthyl; X1=Cl; X2=CH3, Et, n-Pr or n-Bu; R1, R2, R3 are independently selected from H, Me, Et, tBu, F, Cl, Br, OMe or CF3.

2. The flexible monoarylmethyl α-diimine palladium (II) catalyst according to claim 1, characterized in that Selected from the following structures:

3. The method for preparing the flexible monoarylmethyl α-diimine palladium (II) catalyst according to claim 2, characterized in that The synthetic route is as follows:

4. Use of the flexible monoarylmethyl α-diimine palladium (II) catalyst according to claim 1 in catalyzing ethylene polymerization to prepare highly branched polyethylene.

5. The use according to claim 4, characterized in that: The catalytic reaction system also includes sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate.

6. The use according to claim 5, characterized in that: The molar ratio of the flexible monoarylmethyl α-diimine palladium (II) catalyst to sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate is 1:

2.

7. Use of the highly branched polyethylene prepared according to claim 4, 5 or 6 in adjusting the viscosity of poly-alpha-olefin base oil.

8. Use of the flexible monoarylmethyl α-diimine palladium (II) catalyst according to claim 1 in catalyzing the copolymerization of ethylene and polar monomers.

9. The use according to claim 8, characterized in that: The catalytic reaction system also includes sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, methyl acrylate and the like to form a composite catalytic system for the reaction.

10. The use according to claim 9, characterized in that: The molar ratio of the flexible monoarylmethyl α-diimine palladium (II) catalyst to sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate is 1:2.

Citation Information

Patent Citations

  • Large-steric-hindrance flexible diimine ligand, diimine nickel and palladium complexes based on large-steric-hindrance flexible diimine ligand and catalytic application of diimine nickel and palladium complexes

    CN110317149A

  • Pyridine imine ligands, pyridine imine palladium complexes based on the pyridine imine ligands and catalytic application of the pyridine imine palladium complexes

    CN111233755A

Cited By

  • Fully flexible alpha-diimine catalyst and catalytic application thereof

    CN119930879A